2019
DOI: 10.1089/heq.2018.0091
|View full text |Cite
|
Sign up to set email alerts
|

Improving Human Papillomavirus-Related Knowledge and Attitudes Among Ethnically Diverse Young Adults

Abstract: Purpose: To make baseline comparisons and evaluate the efficacy of an intervention designed to improve human papillomavirus (HPV) and HPV vaccine awareness, knowledge, and attitudes among ethnically diverse participants. Methods: Design: Pre- and post-intervention surveys. Setting: An urban, Hispanic-Serving South Florida university. Subjects: Three hundred eighty-seven diverse college students attending a gender stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The HPV infection rate of the youngest group (below 21 years) was high and different from that of Xishuang Banna ( 17), but in line with the data reported in some previous studies (30), suggesting that the higher urbanization may make the young women exposed to HPV infection more easily, which to a large extent may be ascribed to the early sexual activity. Moreover, it indicated that the HPV infection incidence showed a greater trend in the younger population and should not be neglected, indicating that the young people should improve their HPV-related knowledge more deeply for the prevention and intervention for cervical cancer (39).…”
Section: Age Distribution Of Hpv Prevalencementioning
confidence: 99%
“…The HPV infection rate of the youngest group (below 21 years) was high and different from that of Xishuang Banna ( 17), but in line with the data reported in some previous studies (30), suggesting that the higher urbanization may make the young women exposed to HPV infection more easily, which to a large extent may be ascribed to the early sexual activity. Moreover, it indicated that the HPV infection incidence showed a greater trend in the younger population and should not be neglected, indicating that the young people should improve their HPV-related knowledge more deeply for the prevention and intervention for cervical cancer (39).…”
Section: Age Distribution Of Hpv Prevalencementioning
confidence: 99%
“…Quantitative studies of HPV and HPV vaccine-related KABs suggest most adults know about HPV, HPV-related cervical cancer, and HPV vaccines; however, few are aware that HPV causes noncervical cancers or that HPV vaccination is approved for 27-to 45-year-olds (Alber et al, 2021;Thompson et al, 2021). Among adults aged 27 to 45, HPV and HPV vaccine awareness has been found to be positively associated with being a woman, having a higher educational attainment, and having sought cancer information previously (Thompson et al, 2020), whereas studies of younger adults suggest KABs also vary by income, religion, race/ethnicity, urbanicity, and other sociodemographic characteristics (Bodson, Wilson, Warner, & Kepka, 2017;McBride & Singh, 2018;Mohammed et al, 2018;Preston & Darrow, 2019). Positive associations have been identified between adults' intentions to vaccinate and specific KABs, including perceived effectiveness against future HPV infections, perceived benefits from vaccination, perceived autonomy to be vaccinated, and positive attitudes and norms about HPV vaccination (Alber et al, 2021;Thompson et al, 2021).…”
mentioning
confidence: 99%
“…Several instruments have been used in college students without testing the comprehensive psychometric properties to assess attitudes toward HPV vaccination. In the majority of the prior studies (Dany et al., 2015; Kim et al., 2019; Krawczyk et al., 2012; McMann & Trout, 2021; Preston & Darrow, 2019a; Preston & Darrow, 2019b; Stout et al., 2020; Villanueva et al., 2019), attitude instruments have been used without detailed information about the instruments and/or tests of the reliability and validity comprehensively. Thus, it was difficult to know whether those instruments were reliable and valid.…”
Section: Discussionmentioning
confidence: 99%